(untitled) (Economic and Political Thought, 2017)
This paper conducts a comparative review of Bulgaria, Slovakia and Poland’s taxation system performance in pursuit of the question whether the flat tax system was able to meet the hopes reposed in it. The three countries were selected because they nominally contain different taxation systems: Poland has a progressive one; Slovakia has a flat tax while retaining some elements of progressive taxation; whereas Bulgaria has the most radical flat tax system in the region. Furthermore, after a quarter of a century their economic and tax experience does not correspond with the expectations of the flat tax dogma. The research argues that the question whether the taxation system in the region is flat or not is of secondary importance, despite the fact that all the tax systems in their essence aim to perform in a very similar ‘flattened’ taxation pattern. Secondly, that the quest for foreign direct investments cannot be pursued blindly and uncritically, since the three countries’ experience reveals alternative and most importantly, not only positive achievements. Finally, the paper argues that the current performance of the three countries’ taxation systems does not correspond with the expectations that the flat tax system will resolve the internal operational difficulties such as high compliance gaps, tax evasion and weak tax administration. Having in mind that after a quarter of a century the three countries reached different levels of economic development, the question remains whether the current taxation systems are still relevant or they have lost their appropriateness. Poland and Slovakia are approaching the challenge of a ‘middle income trap’, whereas Bulgaria still needs to ‘catch up’. Thus, the former two should reconsider the current pressuring weaknesses of their taxation systems, whereas the latter should reassess its approach towards foreign direct investments and reconsider the direction of its tax policy.